Resource curse: new evidence on the role of institutions - Sarmidi, Tamat; Jafari, Yaghoob; Law, Siong Hook (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2011)
This paper attempts to provide a probable answer to a longstanding resource curse puzzle i.e. why resource rich nations grow at a slower rate compare to the less fortunate one. Using an innovative threshold estimation technique, the empirical results reveal that there is a threshold effect in the natural resources – economic growth relationship. We find that the impact of natural resources are meaningful to economic growth only after a certain threshold point of institutional quality has been attained. The results also shed light on the fact that the nations that have low institutional quality depend much on natural resources while countries with high quality institution are relatively less dependent to natural resources to generate growth.